Growth inhibition of the toxic cyanobacterium Cylindrospermopsis raciborskii by extremely low-frequency electromagnetic fields - Mohamed, Zakaria (Array, 2020)
This study investigates the effects of extremely low-frequency electromagnetic fields (ELF-EMFs) on the growth and antioxidant defence enzymes of the toxic cyanobacterium Cylindrospermopsis raciborskii (Woloszynska) Seenayya et Subba Raju. To determine resonance frequency of growth inhibition of C. raciborskii, cells were subjected to ELF square amplitude modulated waves (QAMW) with a range of frequencies (0.1, 0.3, 0.5, 0.7, 0.9 Hz) at single intensity of 100 V m–1 for 30 minutes. The results revealed that the highest growth inhibition of Cylindrospermopsis occurred upon exposure to 0.7 Hz QAMW for 30 min. ELF-EMF-exposed cultures exhibited a marked decrease in cell number, chlorophyll-a content and activity of antioxidant enzymes compared to control cultures, and this effect increased with the prolongation of exposure time. Moreover, ELF-EMF induced morphological changes in Cylindrospermopsis cells upon exposure to 0.7 Hz QAMW for 120 min, including shrinking and disintegration of cytoplasmic contents, and thickening of the cell wall. Changes in dielectric properties, as a measure of interaction of cellular constituents (e.g., plasma membrane, cell wall and cytoplasm), with electromagnetic fields were also observed for treated cells. Our results provide a new possibility for using ELF-EMFs to eliminate toxic cyanobacteria from drinking and recreational water sources.